1907
DOI: 10.1002/cber.19070400282
|View full text |Cite
|
Sign up to set email alerts
|

Über einige phenylierte Derivate des p, p‐Ditolyls

Abstract: Haven, COIIU, U. S. A. (durch T. R. J o h n s o n rintl G . S. J a m i e s on).Fur die Bibliothek sind als Geschenke eingegangen : J a h r e s b e r i c h t iiber die F o r t s c h r i t t e der Cliemie und rrr-wandter Teile anderer Wissenschaften, begriindet von J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0
2

Year Published

1968
1968
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(113 citation statements)
references
References 2 publications
2
109
0
2
Order By: Relevance
“…In 1907, Chichibabin isolated 2 as a blue-violet compound that reacts readily with oxygen. 12 Many measurements were carried out to characterize the electronic structure of 2, but these studies caused controversial discussions on its spin state: singlet, triplet, or double doublets. Although magnetic susceptibility measurements indicated that 2 is diamagnetic, 13 a solution ESR measurement suggested that ca.…”
Section: ¹1mentioning
confidence: 99%
“…In 1907, Chichibabin isolated 2 as a blue-violet compound that reacts readily with oxygen. 12 Many measurements were carried out to characterize the electronic structure of 2, but these studies caused controversial discussions on its spin state: singlet, triplet, or double doublets. Although magnetic susceptibility measurements indicated that 2 is diamagnetic, 13 a solution ESR measurement suggested that ca.…”
Section: ¹1mentioning
confidence: 99%
“…Whereas in solution, the dominant nuclear relaxation process is almost certainly caused by the anisotropic hyperfine tensor coupled to the rotational brownian motion of the radical [16]. An estimate of Tlv -1 may be obtained by calculating the diagonal elements of the relaxation matrix [16] and for this particular relaxation process the calculation will depend on products of matrix elements of the form (x] Sz(1)I~: (1)…”
Section: Theorymentioning
confidence: 99%
“…Tschitschibabin's hydrocarbon [1] (I) whose structure is shown in figure 1 is said to be formed by treating solutions of the corresponding dichloride with zinc, copper or silver. Such solutions were first examined using static susceptibility techniques which for various reasons failed to detect the expected paramagnetism.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently there is a considerable amount of interest of various research groups in synthesizing Kekulé open shell polyaromatic HC owing to their application in designing spintronic and energy storage devices. [3][4][5][6][7] In most of the cases the molecular structural design of Kekulé open shell polyaromatic hydrocarbons relied on the bases of Tschitschibabin's HC, and the biradicaloid nature of HC appeared as a consequence of loss of quinoidal form upon extending conjugation thereby gaining the aromaticity.…”
Section: Introductionmentioning
confidence: 99%